2006
DOI: 10.1002/ajim.20394
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary fibrosis in a patient with exposure to glass wool fibers

Abstract: Glass wool or vitreous fibers are non-crystalline, fibrous inorganic substances (silicates) made primarily from rock, slag, glass, or other processed minerals. They belong to the man-made mineral fibers (MMMFs) group and their respiratory effects are well described by De Vuyst et al. [1995]. The authors pointed out the absence of firm evidence that exposure to these fibers is associated with lung fibrosis, pleural lesions, or non-specific respiratory disease in humans. Because of this observation, we find it o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
0
6
0
3
Order By: Relevance
“…Guber et al (2006) reported a case of interstitial lung disease with a relatively benign course during the follow-up period of ≥ 4 years. Because of the high percentage of CD8 + T lymphocytes in the induced sputum and BALF, the histologic findings and lung CT–scan changes together indicated a possible active inflammatory process, resembling pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guber et al (2006) reported a case of interstitial lung disease with a relatively benign course during the follow-up period of ≥ 4 years. Because of the high percentage of CD8 + T lymphocytes in the induced sputum and BALF, the histologic findings and lung CT–scan changes together indicated a possible active inflammatory process, resembling pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Carel et al (2007) conducted a multicenter study in Europe to elucidate the extent to which lung cancer burden in men was driven by asbestos and MMVFs, but they did not observe a significant overall increase in risk of lung cancer caused by MMVFs. MMVFs were associated with granulomatous lung disease in humans in some reported cases (Drent et al 2000a, 2000b; Guber et al 2006; Klimczak et al 2000; Takahashi et al 1996; Vahid et al 2007). In an experimental study, Adamson et al (1995) administered a milled fiberglass sample to mice by intratracheal instillation and observed granulomas at bronchoalveolar ducts and morphologic evidence of fibrosis.…”
mentioning
confidence: 97%
“…Die Fasern wurden chemisch analysiert und als Glaswoll fasern identifiziert. Der Mann war langjährig gegen Glaswollfasern exponiert (Guber et al 2006 (Greillier und Astoul 2008). Pleuraplaques sind in der Regel ohne funktionelle Relevanz (Pairon et al 2013(Pairon et al , 2014 und gelten als Marker für eine Faserexposition.…”
Section: Befunde Zu Anderen Mineralfasernunclassified
“…La mayoría de los resultados no mostraron patrones de fibrosis importantes, aunque en algunos de estos estudios no se encontraba bien definido el periodo de exposición, el tipo de fibra ni el control de posibles sesgos asociados al consumo de tabaco o a la exposición a otros agentes como amianto. La mayoría de los estudios no permiten establecer una relación clara entre la exposición a fibras de vidrio y su posible efecto fibrinógeno, aunque tampoco es posible excluir que no exista esta relación en determinados casos concretos de exposición 18 y podemos encontrar literatura científica que describe algunos casos de patología compatible con fibrosis pulmonar en trabajadores expuestos a determinadas fibras o lanas de vidrio [19][20][21][22] .…”
Section: Fibrosis Pulmonar Y Lesiones Pleuralesunclassified